Responsible and Sustainable Tourism - Lessons from Latin America and the Caribbean - Ortiz, Diana; Solo, Tova Maria (World Bank, Washington, DC, 2012)
Urban and rural local development projects share common goals with tourism insofar as they aim to improve the quality of life, the attractiveness of locales and to increase economic opportunities and incomes for residents. In Santa Rosa de Copan a World Bank financed project has reinforced links between the city and the nearby archeological site of Copan in Honduras, building pathways, reception areas, and providing signage and guides to the ruins and to the city as well. The Santa Rosa project has also reinforced local governance, by developing a meaningful role for the municipality with the Archeological Institute of Honduras and the Ministry of Tourism. Finally, it has established a special program to offer locally-owned tourism products with marketing, certification and access to credits and small grants. Projects in Lake Titicaca, Bolivia, Puerto Limon, Costa Rica and Vilcanota Valley, Peru have also invested in the cities' rich cultural history, while projects in Mexico and the Peruvian lowlands have developed tourist destinations in rural communities, improving local quality of life, and local incomes.